Kualitas Pelayanan Pendidikan di TK Aisyiyah Kota Sukabumi: Strategi Pendekatan Metode Service Quality - Lastriyani, Indri; Lidiawati; Sauri, R.Supyan; Wasliman, Iim (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This study delves into the satisfaction level of parents regarding the educational services provided by Aisyoyah Kindergarten in Sukabumi City. There are five dimensions of educational services: Tangibles (Physical Evidence), Reliability, Responsiveness, Assurance, and Empathy. The research addresses two main questions: (1) To what extent are parents satisfied with the educational services at Aisyoyah Kindergarten in Sukabumi City? (2) How does Aisyoyah Kindergarten in Sukabumi City enhance strategies to satisfy parents regarding educational services? This is a descriptive study employing a quantitative approach. The research subjects include parents of students from classes A and B at Aisyoyah Kindergarten in Sukabumi City, with a sample size of 36 from a total population of 61 students. Data collection techniques encompassed questionnaires, documentation, and interviews. Based on the research findings, it can be concluded that the satisfaction level of parents concerning educational services, covering the dimensions of Tangibles or Physical Evidence, Reliability, and Assurance, at Aisyoyah Kindergarten in Sukabumi City stands at 75%, falling under the category of "Satisfied." The data analysis technique used is service quality, which determines the value of the gap between perception and performance and ranks the gap value. Highest to lowest, and a Cartesius diagram. Aisyiyah Kindergarten in Sukabumi City aims to enhance the quality of educational services and elevate parental satisfaction by (a) improving the school's human resources, including educators and education personnel supporting the School Principal in advancing school quality, (b) providing adequate school facilities and infrastructure, especially in the realm of teaching and learning activities, (c) enhancing the professionalism of teachers within the school, (d) conducting specialized development activities for high-achieving students, (e) establishing standards for academic achievement to attain educational quality, and (f) managing school funds.